2022
DOI: 10.1016/j.heliyon.2021.e08657
|View full text |Cite
|
Sign up to set email alerts
|

Effect of lime on selected soil chemical properties, maize (Zea mays L.) yield and determination of rate and method of its application in Northwestern Ethiopia

Abstract: Soil acidity is the major soil chemical constraint that limits agricultural productivity in the highlands of Ethiopia receiving high rainfall. This study was conducted to evaluate the effect of different lime rates determined through different lime rate determination methods on selected soil chemical properties and yield of maize ( Zea mays L. ) on acidic Nitisols of Mecha district, Amhara Region, Ethiopia. The experiment had 10 treatments (0, 0.06, 0.12, 0.18, 1, 2, 3.5, 4, 7 and 14 ton… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
14
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 15 publications
5
14
1
Order By: Relevance
“…In the present study, liming and fertilization almost doubled the available phosphorus at the 0-30 cm depth. This result is similar to the results reported by Alemu et al [29], for the same dose of lime. Total cation exchange capacity did not change with the addition of lime in the present study, which contradicts the results of previously reported studies [29,30].…”
Section: Effect Of Liming On Soil Characteristicssupporting
confidence: 93%
See 3 more Smart Citations
“…In the present study, liming and fertilization almost doubled the available phosphorus at the 0-30 cm depth. This result is similar to the results reported by Alemu et al [29], for the same dose of lime. Total cation exchange capacity did not change with the addition of lime in the present study, which contradicts the results of previously reported studies [29,30].…”
Section: Effect Of Liming On Soil Characteristicssupporting
confidence: 93%
“…This result is similar to the results reported by Alemu et al [29], for the same dose of lime. Total cation exchange capacity did not change with the addition of lime in the present study, which contradicts the results of previously reported studies [29,30]. The application of 1 t•ha −1 of lime decreased organic carbon content [29] from 2.19% to 1.89% (more than 15%) in Ethiopia.…”
Section: Effect Of Liming On Soil Characteristicssupporting
confidence: 93%
See 2 more Smart Citations
“…The occurrence of soil acidity is identified as one of the major issues limiting the yields of many crops worldwide (Abdalla et al., 2022; Adane, 2014; Agegnehu et al., 2021; Alemu et al., 2022; Farina et al., 2000). Soil acidity impacts several biochemical reactions that control the availability of many essential plant nutrients, but in some cases, it also causes toxicity of certain micronutrients in soils (Ahmed et al., 2022; Alemu et al., 2022; Mahmud & Chong, 2022). On a global scale, FAO (2022) reported that soil acidity affects nearly 4 billion hectares of land area, corresponding to almost 30% of the ice‐free agricultural land worldwide.…”
Section: Introductionmentioning
confidence: 99%